The Effect of Tax Planning and Temporary Difference to Earnings Management - Cindy Lystia Tartono; Athalia Ariati Hidayat; Luciana Haryono (Journal of Applied Accounting and Taxation, 2021)
This study aims to analyze tax planning (tax planning is estimated using effective tax rate) motivations that push management (agent) to manage earnings and the ability of temporary difference accounts (measured by deferred tax assets, liabilities and expenses) to detect earnings management. Earnings management is estimated using the modified jones model. This study uses three independent variables to measure temporary difference, analyzes the effect of the independent variables towards the direction of earnings management and analyzes more than one industry so the results Samples used in this study are 377 non-financial public firms that are listed in the Indonesia Stock Exchange from 2015 until 2019, with a total of 1,832 observations. The data panel is processed using multiple linear regression using fixed effect model. The results of the study found only deferred tax liabilities has significant impact to earnings management and is able to detect earnings management upwards. Tax planning only effects absolute earnings management without specific direction. Deferred tax assets do not have a significant impact to detect earnings management downwards and deferred tax expense has no significant impact to earnings management but can potentially detect earnings management upwards in extreme cases.Deferred Tax Asset